Leaving Care: Unaccompanied Asylum- Seeking Young Afghans Facing Return - Kim Robinson; Lucy Williams (Refuge, 2015)
Unaccompanied asylum-seeking children in the United Kingdom approach adulthood knowing that they will be encouraged or even forced to return to their countries of birth. Drawing on a project that promoted voluntary return to Afghanistan, we use interviews with twelve young people, professionals working in the Home Office and in education, local authorities, and voluntary-sector agencies to describe a complex area of immigration policy. We show how the state’s obligations as “corporate parent” clash with increasingly punitive migration controls and with growing political scrutiny of public spending. We propose education as a way to prepare young people for futures as global citizens in either country of settlement or of origin.